Bridging the motivation gap: Multi-stakeholder perspectives on science learning barriers and evidence-based solutions in Indonesian elementary schools - Sri Lestari Kadarsih; Suyono Suyono (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2026)
The low science learning outcomes in elementary schools remain a persistent challenge globally, particularly in developing educational contexts. This study addresses the problems in science learning in Indonesian elementary schools. Data were collected from 32 fifth-grade students and one teacher at SDN 2 Blimbing Klaten during October 2025, employing a qualitative descriptive approach. Findings revealed that low student motivation, characterized by limited engagement and activity levels, coupled with monotonous teaching methods and limited media variation, represent key barriers to effective science learning. These findings align with international research demonstrating the critical importance of student-centered approaches and diverse instructional strategies. Implications for policy and practice are discussed in relation to contemporary international frameworks for science education reform.